Hematotoxicity of magnetite nanoparticles coated with polyethylene glycol: in vitro and in vivo studies. Issue 6 (1st October 2015) - Ruiz, A.; Ali, Lamiaa M. A.; Cáceres-Vélez, P. R.; Cornudella, R.; Gutiérrez, M.; Moreno, J. A.; Piñol, R.; Palacio, F.; Fascineli, M. L.; de Azevedo, R. B.; Morales, M. P.; Millán, A.
Graphical Abstract: Abstract: Hematotoxicity of magnetite nanoparticles coated with dimercaptosuccinic acid (DMSA) and polyethylene glycol (PEG) has been evaluated by determining their safety in vitro and in vivo in a rat model up to 30 days after administration of a single dose. The in vitro analysis consists of global plasma coagulation (PT, aPTT, and fibrinogen) and platelet aggregation tests while the hematotoxicity studies in vivo include a complete blood count and the possible genotoxic effect analysis in the bone marrow hematopoietic function. Prolonged aPTT values indicate a higher anticoagulant effect for NP-DMSA compared with PEG-coated nanoparticles as a consequence of the higher surface charge of the former. The in vivo tests showed that these bioferrofluids do not cause genotoxic effects, affect erythropoiesis or increase the number of immature erythrocytes in the bone marrow at the analyzed dose. However, nanoparticle administration showed a significant effect on the leukocyte counts in animals treated with DMSA coated nanoparticles 24 h after injection. This response is not observed in animals treated with PEG modified nanoparticles which justifies the use of this polymer in biomasking strategies.